Interpretation, Inclusiveness, and Ambiguity: A Critique of Rule Design in Modern Legal System - Muhamad Pelengkahu (The Indonesian Journal of International Clinical Legal Education, 2025)
This paper analyzes three critical concerns in the formulation of contemporary legal regulations: the propensity for over- or under-inclusiveness, ambiguity in application, and interpretive difficulties. This study utilizes a normative-doctrinal legal methodology within an interdisciplinary framework, incorporating jurisprudence, legal linguistics, and regulatory theory, to argue that rules function not solely as normative instruments but as socio-linguistic constructs shaped by power dynamics and interpretive communities. The intrinsic abstraction and prescriptive characteristics of legal language led to ambiguity and practical uncertainty. This paper challenges the formalistic assumptions inherent in traditional rule-making through a conceptual examination of the difference between rules and standards and a multidimensional exploration of rule typologies, including legal status, language structure, and normative power. The research moreover suggests strategic methods to enhance regulatory efficacy and flexibility, including the formation of interpretative communities and the implementation of goal-oriented regulatory frameworks. The findings seek to enhance the development of regulatory systems that are contextually adaptive and normatively consistent, providing insights for improved legal rule formulation in evolving social contexts.